HUBUNGAN POLA KOMUNIKASI ORANG TUA DENGAN PENGETAHUAN DAN SIKAP KESEHATAN REMAJA DI DESA LANGA KECAMATAN SYAMTALIRA BAYU KABUPATEN ACEH UTARA - Fatiyani Fatiyani; Erlina Erlina; Yenny Fitri Wahyuni (Media Bina Ilmiah, 2023)
Adolescents or Teenagers are a unique and critical phase in each stage of individual life. This phase is a phase of transition from children to adult individuals, which can be seen from physical and psychosocial changes that bring positive opportunities as well as negative risks that will impact the future. Health and social problems must receive real attention, especially reproductive health problems. In Indonesia, 2.6% of first marriages are made at less than 15 years of age and 23.9% of first marriages are at 15-19 years of age. The rate of pregnancy in adolescents under 15 years of age was 0.02% and pregnancy in 15-19 years was 1.97%.Communication between parents and adolescents about reproductive health is essential, especially in reducing risky sexual behavior. The design of this study used a quantitative depcriptive analytic method. The instrument used is a questionnaire. The population is teenagers aged 10-19 who live in Langa Village, Syamtalira Bayu, North Aceh. The sample size is calculated using Solvin's formula of 30 people. The chi-square statistical test results between parent communication patterns and adolescent knowledge of adolescent health are obtained by a value p = 0.001, then a value < 0 0.05 means H0 is rejected, so there is a relationship between parent communication patterns and adolescent health knowledge. The test result between the parental communication pattern and the adolescent attitude of the adolescent's health was obtained a value p = 0.001, so the value < , 0.05 means H0 is rejected, so there is a relationship between the parental communication pattern and the adolescent's health attitude. This suggests that adolescents who have difficulty communicating with parents about reproductive health, adolescents tend to have less attitude toward reproductive health, open discussions about sexuality become difficult for both parents and adolescents due to abstinence in social culture. Parents should be the primary source of information and educators